2013
DOI: 10.1155/2013/726872
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Photocatalysis of Well-Dispersible Phase-Pure Anatase TiO2Nanoparticles

Abstract: High-purity anatase TiO2nanoparticles were prepared using an improved sol-hydrothermal method. The as-prepared sample was characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), and UV-vis diffuse reflectance spectra. TEM results showed that the average particle size of all TiO2particles was calculated to be (10±1) nm. The XRD analysis indicated that the present sample was fully crystallized and appeared to be highly phase-pure anatase. The BET analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 16 publications
(16 reference statements)
13
54
0
Order By: Relevance
“…The patterns confirmed that the TiO 2 in TiO 2 -S/rGO hybrid and all the control samples is in the anatase phase57. The results confirmed that anatase phase TiO 2 was successfully synthesized through the single-step hydrothermal method.…”
Section: Resultssupporting
confidence: 62%
“…The patterns confirmed that the TiO 2 in TiO 2 -S/rGO hybrid and all the control samples is in the anatase phase57. The results confirmed that anatase phase TiO 2 was successfully synthesized through the single-step hydrothermal method.…”
Section: Resultssupporting
confidence: 62%
“…In addition, the diffraction peaks denoted as “A” correspond to the (101), (004), (200), (105) and (211) planes. These correspond to the anatase TiO 2 , according to the JCPDS file 21–1272 . This means that the TiO 2 IL is successfully formed from the TiO 2 sol–gel solution without the sintering process.…”
Section: Resultsmentioning
confidence: 84%
“…The characteristics peaks at 2θ ≈ 18.5°, 20.2°, 26.8°, and 39.3° corresponds to (100), (110), (022), and (211) reflections of crystalline plane of PVDF–HFP . The crystalline planes of TiO 2 and ZnO are also noted in Figure (a). It is observed that the peak intensity of PVDF–HFP polymer matrix decreases with addition of IL and further decreases with addition of nanoparticles.…”
Section: Resultsmentioning
confidence: 84%